Persepsi Mahasiswa Prodi Komunikasi Penyiaran Islam Fakultas Dakwah dan Komunikasi Terhadap Olahraga Futsal Perempuan di UIN Raden Fatah Palembang - Arsalan, M Akram; Nuraida; Muslimin (Indonesian Journal Publisher, 2024)
Perception is a process upstream from the senses, namely stimuli that humans receive through the senses and is sometimes called a sensory process. Talking about futsal and women, this issue is still relevant to be raised in this study, this is related to the fact that many people still think that women are not enough able to play futsal. The problem in this research is how students' perceptions are based on social, cultural and religious perspectives as well as campus participation in supporting women's sports activities. The purpose of this research is to find out students' perceptions of female students' participation in women's futsal, to find out students' perceptions about society which still views women's futsal as a taboo, to find out students' perceptions of women's futsal from an Islamic and Islamic perspective or point of view. This research uses a qualitative research method with a descriptive qualitative approach to describe phenomena based on incoming data, interview and documentation data collection techniques. Based on the results of the research and discussion, it can be concluded that the meanings formed can be mapped into 4 things, namely meaning viewed from the background, meaning viewed from the perspective of society and the concept of gender, religious views and Islamic law. Students do not agree that futsal can only be played by men even though society still views women's futsal negatively. According to Islamic views, it is legal as long as there is not much harm in it, the campus is a place for female students to join the sport of futsal